Green Scenarios for Power Generation in Vietnam by 2030 - Nguyen, V. H. M.; Nguyen, L. D. L.; Vo, C. V.; Phan, B. T. T. (Engineering, Technology & Applied Science Research, 2019)
Energy for future sustainable economic development is considered one crucial issue in Vietnam. This article aims to investigate green scenarios for power generation in Vietnam by 2030. Four scenarios named as business as usual (BAU), low green (LG), high green (HG) and crisis have been proposed for power generation in Vietnam with projection to 2030. Three key factors have been selected for these scenarios, namely: (1) future fuel prices, (2) reduction of load demand caused by the penetration of LED technology and rooftop photovoltaic (PV) systems, and (3) the introduction of power generation from renewable sources. The least costly structure of power generation system has been found. CO2 emission reduction of HG in comparison to the BAU scenario and its effect on generation cost reduction are computed. Results show that BAU is the worst scenario in terms of CO2 emissions because of the higher proportion of power generation from coal and fossil fuels. LG and HG scenarios show their positive impacts both on CO2 emissions and cost reduction. HG is defined as the greenest scenario by its maximum potential on CO2 emission reduction ( 146.92Mt CO2) in 2030. Additionally, selling mitigated CO2can make green scenarios more competitive to BAU and Crisis in terms of cost. Two ranges of generation cost (4.3-5.5 and 6.0-7.7UScent/kWh) have been calculated and released in correspondence with low and high fuel price scenarios in the future. Using LED lamps and increasing the installed capacity of rooftop PVs may help reduce electric load demand. Along with the high contribution of renewable sources will make the HG scenario become more attractive both in environmental and economic aspects when the Crisis scenario comes. Generation costs of all scenarios shall become cheap enough for promoting economic development in Vietnam by 2030.